Inspired oxygen fraction after cardiopulmonary bypass: effects on pulmonary function with regard to endothelin-1 concentrations and venous admixture - Reber, Adrian; Budmiger, B.; Wenk, Markus; Haefeli, Walter E.; Wolff, T.; Bein, Thomas; Skarvan, K. (British journal of anaesthesia, 2000)
Twenty consecutive patients undergoing cardiac surgery with cardiopulmonary bypass (CPB) were allocated at random to group 1 (n=10, high inspired oxygen fraction (FIO2) after CPB), or group 2 (n=10, moderate FIO2 after CPB). The effects of each FIO2 on arterial and mixed venous concentrations of endothelin-1 (ET-1) and its precursor, Big ET-1, were measured. Venous admixture was calculated to assess the efficiency of pulmonary gas exchange. Patients whose lungs had been ventilated with a FIO2 of 1.0 (exposure time 70 min) after weaning from the CPB machine had significantly greater arterial and mixed venous Big ET-1 concentrations and venous admixture than patients whose lungs were ventilated with a FIO2 of 0.35. In contrast, ET-1 concentrations in the two groups were not significantly different. A reduction of FIO2 from 1.0 to 0.6 reduced venous admixture without lowering endothelial peptide concentrations. On the first postoperative day all peptide concentrations were similar in the two groups, whereas venous admixture remained non-significantly higher in group 1. A short period of high FIO2 immediately after CPB increases endothelin concentrations and pulmonary venous admixture.